Sistem Pakar Stunting Pada Balita Menggunakan Metode Forward Channing & Naive Bayes - Andrianof, Harkamsyah (Jurnal Sains Informatika Terapan, 2022)
Stunting is a growth problem in toddlers which is characterized by the length or height of the child being below the established standard deviation. The development of pregnant women greatly affects the health and growth of the womb. Problems with fetal development in the womb that result in low birth weight. The length of the baby is also associated with the incidence of stunting. This is also one of the causes of many toddlers experiencing stunting, because the food provided does not show what is called 4 healthy 5 perfect food. By looking at the number of stunting cases in toddlers in the community, an expert system is needed that can assist users in diagnosing stunting more quickly. This expert system research uses data collection techniques directly to the field to collect data by means of data collection techniques as follows; observations, interviews, and library studies. The use of an expert system with the Forward Chaining & Naïve Bayes method in this system can help and make it easier for users to detect stunting in toddlers.